Five First Nations men performing around the big drum
Caption on verso reads: "(6) P.23 100%." Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.